Increasing Knowledge of Herbal Alternative Medicine on Uric Acid Through Whatsapp Media in Muslim Communities in Banyumas Regency - Aris Fitriyani; Abdul Basit (PT Publikasiku Academic Solution, 2023)
WhatsApp is one of the applications that uses the internet that can be used as a communication medium to share information which is now very popular among the public. WhatsApp can prove flexible in operating can adjust to signal conditions and can be used as an alternative medium in its use. To find out the level of knowledge the public has about alternative medicine against gout can be used, one of them is the WhatsApp application. This study is to determine the difference in knowledge before and after counseling using WhatsApp media. The method used is quasi-experimental with a pre-post test design without a control group design. This research was conducted in Sokaraja District with a population of 900 people. Sampling was carried out by simple random sampling determined based on Cohen Manion and Morrison's table, which amounted to 209 respondents. Data were collected through questionnaires and analyzed using the Wilcoxon Test. The results of the study showed differences between before and after the intervention with p-value = 0.000